Identification of quercetin compounds in cabbage (Brassica oleracea var. capitata L.) and mustard greens (Brassica juncea L.) from Malang Regency - Permana, Fendy Hardian; Rakhma, Zulfaza A-Janah; Latifa, Roimil (Universitas Islam Negeri Sumatera Utara, 2025)
Free radicals are chemical molecules with an unpaired electron in their outermost orbit. Free radicals are often referred to as Reactive Oxygen Species (ROS) which have reactive and labile properties so they tend to capture electrons from other molecules. Unhealthy lifestyles have a very high risk of increasing free radicals in the body. The imbalance of antioxidants with free radicals entering the body will cause oxidative stress. Consuming healthy foods, one of which is vegetables, is an effort that can be made to maintain a healthy body. The abundant production of cabbage and mustard greens in Malang Regency is expected to provide good benefits to help ward off excess free radicals. Quercetin compounds are one of the most common compounds found in plants and contain good antioxidants. The purpose of this study was to identify the content of quercetin compounds in cabbage (Brassica oleracea var. capitata L.) and mustard greens (Brassica juncea L.) in Malang Regency. The method used is the quercetin compound test, with measurement performed using a UV-Vis spectrophotometer to determine the levels of compounds in cabbage and mustard greens extracts. The results of the study showed that after adding HCl reagents and Mg powder to cabbage and mustard greens, a dark red color change occurred, indicating that the results were positive for quercetin compounds. Measurements using a UV-Vis spectrophotometer obtained quercetin compound levels in cabbage (Brassica oleracea var. capitata L.) of 358.34 ppm or 3.5% and mustard greens (Brassica juncea L.) of 360.87 ppm or 3.61%.